PENGARUH KUALITAS AUDIT TERHADAP EARNINGS MANAGEMENT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Amanda Ayuputri; Felizia Arni Rudiawarni; Muhammad Wisnu Girindratama (Jurnal Akuntansi Trisakti, 2023)
The purpose of this study is to examine the effect of audit quality proxied by the size of the auditor, auditor industry specialization and audit tenure on earnings management. Earnings management is proxied by discretionary accruals. This study uses three control variables, which are firm size, operating cash flow ratio, and leverage. This study uses secondary data derived from the financial statements of listed companies on the Indonesia Stock Exchange from 2017-2019. Based on the purposive sampling method we obtain 366 observations, and the technique for examining the hypothesis is multiple regression analysis. The results show that audit quality has no significant effect on earnings management. However, this study finds that Big 4 audit quality and auditors of industry specialization moderated the relationship between cash flow from operations and earnings management, while leverage moderates the relationship between Big 4 audit quality and earnings management.